MANIFESTASI DAN PENATALAKSANAAN PEMFIGUS VULGARIS DI RONGGA MULUT - Indra Gunawan; Riani Setiadhi (Universitas Baiturrahmah, 2015)
Background : Pemphigus Vulgaris (PV) is an autoimmune intraepithelial blistering disease involving the skin and mucous membranes. Oral lesions could be the first sign of the disease followed by the involvement of skin and other mucosa sites.Objectives : This is oral manifestations of pemphigus vulgaris case report, intended to help clinicians to recognize and treat the oral lesions.Case Reported : Male 27 yo admitted to RSUP Dr.Hasan Sadikin hospital with multiple blisters on the skin and oral mucosa, was diagnosed with Pemphigus Vulgaris.Case Management : Patient was treated with steroid mouth wash and oral paste. After two months of treatment, the patient was fully recovered from oral lesion.Discussion : In PV, autoantibodies are produced against desmosomes spesifically desmoglein 3 which responsible for holding the cells of the epithelium together. The loss of adhesive function due to anti Dsg 3 antibodies result in bulla formation on the oral mucosa.The aetiology for PV is still uncertain. Conclusion :Early recognition and treatment of oral lesions is important as it may prevent skin involvement. Early treatment, patient’s compliance and multi disciplinal teamwork ensure the treatment succes for this disease